An Initial Assessment of the Utility of Validated Alcohol and Drug Screening Tools in Predicting 30-Day Readmission to Adult General Medicine Wards. (July 2018) - Gerke, Steven P.; Agley, Jon D.; Wilson, Cynthia; Gassman, Ruth A.; Forys, Philip; Crabb, David W.
Previous studies have identified drug and alcohol use as risk factors for readmission using claims data, but not by using substance use screening scores. This preliminary study tested the hypothesis that prevalence of 30-day readmission would be higher among patients screening positive on the 10-item Alcohol Use Disorders Identification Test (AUDIT-10) or the 10-item Drug Abuse Screening Test (DAST-10) tools at intake than among the general patient population. Social workers screened 4708 adult inpatients using prescreening questions followed by the AUDIT-10 and/or DAST-10. Patients with positive screens were followed for readmissions within 30 days of discharge. A positive screening score on the AUDIT-10 or DAST-10 instrument at intake was associated with higher risk of readmission to the general medicine wards within 30 days; this relationship appears complex and subject to mediation. Post hoc chart review found that the majority of readmissions among patients with positive screens were not immediately attributable to substance use. Further study is needed to verify these preliminary findings.